Analisis Consumer Behavior, Service Quality, Company Image, And Price Terhadap Purchase Decision Menggunakan Aplikasi Go-Jek Fitur Go-Food Di Masa Kebiasaan Baru (Studi Pada Karyawan Pt. Citra Adi Sarana Indonesia Cabang Gresik) - Abdul Ghofur; Abid Muhtarom; Noer Rafikah Zulyanti; Miftakhul Arif (Trunojoyo University of Madura, 2022)
The development of the world of transportation in modern times is growing rapidly. This is evidenced by the number of transportation services that have followed the times, for example the transportation application that is widely used by the community, one of which is Go-Jek. Go-Jek is widely used for transportation services other than as a transportation service to take someone to their destination. But Go-Jek is now used for food delivery services called Go-Food. The object of this research is a study at Karywan PT. Cita Adi Sarana Indonesia, Gresik Branch. This research is quantitative in nature by providing questionnaire data to the sample of researchers. This is the sample of researchers as many as 60 people. The analytical tools in this study are validity, reliability, classical assumptions, multiple correlation, multiple linear regression, coefficient of determination, t test, and F test. Service quality (X2), company image (X3), and price (X4) have tcount ttable, namely Consumer Behavior tcount 2,374 ttable 2,004, Service Quality tcount 2,278 ttable 2,004, Company image tcount 2,288 ttable 2,004, and Price tcount 2.683 t table 2.004 means that the results are considered that all independent variables partially influence the Purchase Decision. In the F test, it states that Fcount Ftable, namely 20.234 2.54, which means that the independent variable has a silmutan effect on Purchasing Decisions. In this study, the linear regression equation is Y = 0.158 + 0.246X1 + 0.281X2 + 0.241X3 + 0.251X4, which means that the Service Quality (X2) variable is the most dominant variable in purchasing decisions. This is based on the results of the regression value which is greater than the value of the other independent variables, namely 0.281.